Integrating Andragogy Principles in Arabic Learning: A Study on Higher Education Students - Nur Toifah; Mohammad Samsul Ulum; Zakiyah Arifa (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study aims to evaluate the outcomes of Arabic language learning based on andragogical principles among students at UIN Maulana Malik Ibrahim Malang. The focus is to determine the effectiveness of the learning process and the extent to which adult learning principles are implemented in improving student learning outcomes. A quantitative approach with a descriptive design was employed. Data were collected באמצעות a structured questionnaire distributed to 520 first-year students selected through random sampling. The instrument measured students’ perceptions of the Arabic learning process grounded in andragogical principles. Data were analyzed using descriptive statistics to determine overall performance levels.The findings indicate that the implementation of andragogical principles in Arabic learning achieved a mean score of 84.51, categorized as “excellent.” A majority of respondents (80.77%) reported experiencing the learning process at an excellent level, while 19.23% rated it as good, indicating overall satisfaction above average standards. The approach demonstrated several strengths, including the promotion of discussion, collaboration, and learner autonomy. However, challenges were also identified, particularly the diversity of students’ prior experiences and the need for additional time to adapt learning materials, especially in large classroom settings.In conclusion, the application of andragogical principles in Arabic language instruction has proven to be highly effective in enhancing student learning outcomes. Nevertheless, optimizing its implementation requires addressing learner diversity and adapting instructional strategies to accommodate varying needs, particularly in large-group contexts.